Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai di Kantor Badan Perencanaan, Penelitian, dan Pengembangan Daerah (BAPPEDA) Provinsi Gorontalo - Kalaati, Nurain Oktaviani; Sulila, Ismet; Mozin, Sri Yulianty (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
This study aimed to determine the influence of work discipline on employee performance at the Regional Planning, Research, and Development Agency (BAPPPEDA) of Gorontalo Province. Data were collected through observation, documentation, and questionnaires distributed to employees at the Regional Planning, Research, and Development Agency (BAPPEDA) office. The data were analyzed using quantitative methods. The study results showed that work discipline significantly and positively influenced employee performance, with a coefficient of determination of 42.1%. This indicates that work discipline significantly influences employee performance by 42.1%, while the remaining 57.9% is influenced by other factors. Therefore, future studies should consider adding other independent variables that are not included in this study.